Author Correction: Using a smartphone-based self-management platform to support medication adherence and clinical consultation in Parkinson's disease. (December 2017) - Lakshminarayana, Rashmi; Wang, Duolao; Burn, David; Chaudhuri, K.; Galtrey, Clare; Guzman, Natalie; Hellman, Bruce; James, Ben; Pal, Suvankar; Stamford, Jon; Steiger, Malcolm; Stott, R.; et al.
In the original version of this article the copyright notice was missing from Tables 1 and 3. This has now been added alongside the three relevant references inserted as refs. 21–23. The correction has been published and is appended to both the HTML and PDF versions of this paper. The errors have been fixed in the paper.